4-Methyl-N-(3-methylphenyl)benzenesulfonamide - Nirmala, P. G. (International Union of Crystallography, 2009)
In the title compound, C(14)H(15)NO(2)S, the conformation of the N—C bond in the C—SO(2)—NH—C segment has gauche torsion angles with respect to the S=O bonds. Further, the conformation of the N—H bond is anti to the 3-methyl group in the aniline benzene ring. The molecule is bent at the N atom with a C—SO(2)—NH—C torsion angle of 56.7 (3)°. The dihedral angle between the benzene rings is 83.9 (1)°. In the crystal, intermolecular N—H⋯O hydrogen bonds pack the molecules into a supramolecular structure.